HUBUNGAN PELATIHAN DAN MOTIVASI TERHADAP PRODUKTIVITAS KERJA KARYAWAN PADA PT. PLATINA MULIA ABADI MEDAN - Ferry Safriandi; Windy Aginta (JURIKOM (Jurnal Riset Komputer), 2016)
Training is an activity to improve a person's ability to work. Motivation termed as encouragement. Training and good motivation is a supporting factor to achieve productivity. Based on these descriptions, the formulation of the problem in this research is how the relationship between the training and motivation to work productivity of employees at PT. Platina Mulia Abadi Medan. The theory used in this research is the theory of human resource management related about the training, motivation, and employee productivity therein including the understanding, the importance, the factors that affect the benefits and objectives and indicators - indicators that affect the variables of training, motivation and employee productivity. The research method that I use in this study is a quantitative or qualitative. This type of research is descriptive quantitative nature of the research is associative, data collection methods used, questionnaires, study of documentation, interviews, and observations. The population in the study were 110 employees, and a sample obtained by using the formula slovin amounted to 52 employees. Data processing using software SPSS 23. Data analysis technique used is multiple linear regression, test the coefficient of determination (R2), partial test (t test), simultaneous test (F test). The results obtained by the formulation of regression Y = 22.943 + 0.582 X1 + 0.032 X2, so that the variable training and motivation can improve employee productivity. Results obtained determination coefficient R value (R-square) of 0.210 or 21%, this indicates that the training and motivation related to the employee's productivity by 21% is influenced by other variables not examined by the author. F test results obtained Fcount > Ftable (6.529 > 3.18), it can be concluded that the training and motivation simultaneously or jointly related to work productivity. T test results obtained to training tcount > ttable (3.546 > 1.67), it can be concluded training variable partially related to work productivity of employees at PT. Platina Mulia Abadi Medan, and the t test results obtained for motivation tcount < ttable (0.267 < 1.67), it can be concluded partial motivation variable is not related to work productivity of employees at PT. Platina Mulia Abadi Medan.